Tag-araw ng mga ibong hilaga summer of the north birds - Evasco, Eugene Y. (Lungsod ng Quezon LG & M Corp., 2011)
"Children are not often considered when issues that affect them like the environment and ecology are discussed. But, this wonderful story by the author shows,that it can make a difference in changing adult mindsets and transforming their own areas into sustainable environments. This story is a call to action and a great introduction to the Candaba swamps and the many different migratory birds that visit yearly; that we have re-named and called our very own." Carla M. Pacis.
Donated by Prof. Eugene Yambot Evasco.
Carlos Palanca Memorial Awards for Literature 2005: First Prize, Maikling Kuwentong Pambata.